Physical characteristics and fertility of fractionated donkey semen cooled at 5°C - Carvalho, L. E.; Silva Filho, J. M.; Palhares, M. S.; Sales, A. L.R.; Gonczarowska, A. T.; Oliveira, H. N. [UNESP]; Resende, M. C.; Neves, M. G.; Madison, R. J. (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate the effect of two different extenders (Skimmed Milk Glucose-SMG or Lactose-Egg Yolk-LEY) on physical characteristics and fertility of fractionated donkey semen cooled at 5°C. For this, four Pega donkeys were used as semen donors. The sperm rich fraction of the ejaculate was diluted preparing insemination doses containing 400 x 106 motile spermatozoa in a volume of 22 mL, cooled to 5°C and stored up to 48 hours in a container proposed by Palhares (1997). Sperm motility and vigor were assessed in fresh semen, after first semen dilution, before insemination, at 24 and 48 hours after storage. For the fertility evaluation, 44 mares were inseminated with semen stored for a period between 12 and 24 hours. The mares were inseminated on fixed days (Mondays, Wednesdays, and Fridays) after the detection of a follicle greater than a 30mm diameter in one of the ovaries through ovulation. Pregnancy diagnosis was performed on day 12 post-ovulation, using transrectal ultrasonography. Semen diluted in SMG showed superior sperm motility than LEY, at the Pre-AI evaluation (P<0.05). At 48 hours of storage, all donkeys had motility values between 45 and 53% for semen diluted in SMG, while only one donkey showed motility greater than 30% in the LEY treatment. The pregnancy rate/cycle for mares inseminated with semen diluted in SMG was superior than that obtained using LEY (56.52% vs 4.76%, respectively).
Keywords: Cooled semen; Donkey; Fertility; Fractionated collection